Typology and its Usage in Different Disciplines - Manuchehr, Saloxiddinov (Journal of Ethics and Diversity in International Communication, 2023)
What is typology? The term typology refers to studying, examining, classifying, or analyzing things or concepts according to different types or categories. Before reviewing typology examples, it's important to really understand the definition of typology. Understanding what typology is will make it easier to understand how certain examples illustrate the concept. A typology is simply a means of classifying items, people or concepts by general type. The word typology is simply a scientific term, which is used for grouping things together based on similarities. Typology can be used across all industries and disciplines. A few examples of fields in which typology is used include linguistics (as a linguistic typology or language typology), theology, anthropology, archaeology, psychology, politics, education, medicine, farming, and many others.